RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - BATYGIN, YURIY; YERYOMINA, OLENA; SHINDERUK, SVITLANA; CHAPLYGIN, EVGEN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Reliable assessments of the state of modern energy show the relevance of scientific and technical developments aimed at solving its problems. In this regard, the use of resonance phenomena in electrical circuits with active-reactive elements acquires particular significance. Their various combinations open up exceptional opportunities for creating fundamentally new efficient energy sources. This article discusses a resonant active electrical power amplifier containing a sequence of several electrically connected active-reactive circuits, which, depending on the purpose, are excited in the voltage resonance or current resonance mode. An equivalent circuit is proposed for the proposed resonant amplifier of active electrical power, represented by two blocks, each of which consists of a sequence of inductively coupled active-reactive circuits excited at the same frequency. Calculations are presented showing the theoretical justification for the performance of the proposed scheme. The analysis of ongoing electromagnetic processes was carried out using well-known methods of the theory of electrical circuits without involving any hypotheses about the physics of resonance phenomena. It is shown that in the proposed amplifier circuit, the first block amplifies the reactive power of the harmonic signal with a high conversion coefficient, the second, with a slight gain, converts the reactive power of the harmonic signal into active power. The results of calculations are presented, illustrating the functional dependence of the integral gain on the main characteristics of the output resonant circuit. Numerical estimates of the main characteristics of the proposed circuit showed that with an appropriate choice of its parameters, high values of the output characteristics are possible, so the gain can reach a value of 48. The significance of the results obtained for practice lies in their use for formulating recommendations for the creation of real efficient sources of electrical energy, the principle whose actions are based on the use of natural resonance phenomena.